A multiview approach to the tribological characterisation of cutting tool coatings for steels in high-speed dry turning. (15th August 2006) - Rech, J.
The use of thin hard coatings in cutting applications has become almost systematic. The paper summarises and discusses the use of various physical and mechanical tests to obtain a general characterisation of the frictional properties of a coating dry cutting of steels. The limitations of standard methods to reach appropriate conditions (high velocity, temperatures, and pressures) is underlined. The necessity to conduct characterisations during the cutting process itself appears clearly to qualify the modifications of the tribological system. The following aspects have been monitored: chip formation mechanisms, cutting forces, interface temperature and heat flux measurements. The experiments have been applied on the characterisation of the frictional behaviour of a reference coating such as TiN, and of new coatings such as (Ti, Al)N and (Ti, Al)N+MoS2, deposited on a WC-Co carbide substrate during the machining of steels. Finally, the previous investigations have been correlated with wear tests in high speed dry turning.